IMPROVEMENT OF SCIENCE PROCESS SKILLS THROUGH LEARNING CYCLE STRATEGY BASED ON LESSON STUDY IN THE MATERIAL OF HUMAN-ANIMAL CIRCULATION - Aswin, Pani; Gafur, Abdul; Rahayu, Sri; Karyadi, Bhakti (Universitas Negeri Yogyakarta, 2019)
This research is a classroom action research. The purposes of this study are (1) describing the activities of Lecturers and Students in Human-Animal Physiology courses on circulation material with the 5E learning cycle strategy; (2) describing students' science process skills in Human-Animal Physiology courses on circulation material with learning cycle strategy. The research method used is descriptive, to describe the activities of Lecturers and Students as well as science process skills. The data analysis technique used is quantitative-qualitative descriptive analysis. The results of the study show that (1) the implementation of the syntax of the 5E learning in the first cycle is 86.5% and the second cycle is 93.3%; (2) the value of science process skills in the first cycle is 73.3% and the second cycle is 82%. There are differences in the average implementation of the learning cycle 5E syntax and the science process skills between cycle I and cycle II.